PERAN UDANG VANAME DALAM MENINGKATKAN DAYA SAING EKSPOR PERIKANAN INDONESIA DI PASAR GLOBAL - Arina Lutfatul Latifah; Muhamad Revaldi; Mutiara Nurrizqa Destianty (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Vaname shrimp (Litopenaeus vannamei) has become one of Indonesia's leading fisheries commodities which plays an important role in increasing the competitiveness of fishery exports in the global market. This research aims to analyze the export competitiveness of vaname shrimp as Indonesia's superior product to the United States and Japan markets. The data used in this research is secondary data sourced from Trade Map with HS code 030617 from 2012 to 2022. The analytical tool used is the Revealed Comparative Advantage (RCA) method. The research results show that Indonesian vaname shrimp exports to the United States and Japan markets are competitive, due to better quality and quality. Overall, the success of Indonesian vaname shrimp exports to the US and Japan has contributed greatly to the country's foreign exchange earnings and strengthened Indonesia's position in the global market. Efforts to improve production quality, apply environmentally friendly cultivation technology, and comply with international standards are very important to ensure the competitiveness of vaname shrimp in these markets.